(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Agritourism is another concept of tourism. The objective of agritourism is to get closer to nature. The infrastructure of the agritourism centre is completely different compared to the luxury Hotels. Agritourism centres do not have a great ambiance or many facilities. Most of these centres have average ambiance and limited facilities. In these centres, tourists can take active participation in activities related to farming. Activities such as sowing, farm animal rearing, bird watching, harvest demonstration, bullock cart ride etc. The objective of the research is to identify the challenges of agritourism centres. Majorly there are two types of challenges, first is financial challenges and second is labor challenges. An exploratory research method is applied to identify the challenges faced by the agritourism centres. Research also compares the challenges of agritourism centres in Pune and in the Satara districts. Research is based on primary data. There are total 33 centres in Western Maharashtra that have completed more than 5 years, of which 27 agritourism centres are considered for the study. Data is collected by a personal visit by the researcher to every agritourism centre. For the processing of primary data, SPSS software is used. Descriptive as well as inferential statistics is applied. The expected outcome of the research is there are significant challenges in both areas, financial as well labor, which affect the sustainability and growth of agritourism centres.